2010
DOI: 10.1111/j.1548-1425.2010.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

The cachet dilemma: Ritual and agency in new Dutch nationalism

Abstract: In 2006, the Dutch government introduced a naturalization ceremony for foreigners wishing to become Dutch citizens. Local bureaucrats who organize the ceremony initially disapproved of the measure as symbolic of the neonationalist approach to migration. I analyze how their criticism is undermined in the process of designing the ritual, the form of which continues to express a culturalist message of citizenship, despite organizers’ explicit criticism or ridicule. Using the concept of “cultural intimacy,” I show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 10 publications
0
41
0
1
Order By: Relevance
“…Some studies have identified a paradox between the dominance of Dutch exclusive national discourse, and the growing obligation imposed on migrants to belong to and prove their loyalty to Dutch society (Reekum and Duyvendak 2012;Verkaaik 2010). Buitelaar and Stock (2010) refer to the conflicting demands that Muslim migrants are confronted with (mandating assimilation yet referring to them solely as Muslims) as a "double bind".…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified a paradox between the dominance of Dutch exclusive national discourse, and the growing obligation imposed on migrants to belong to and prove their loyalty to Dutch society (Reekum and Duyvendak 2012;Verkaaik 2010). Buitelaar and Stock (2010) refer to the conflicting demands that Muslim migrants are confronted with (mandating assimilation yet referring to them solely as Muslims) as a "double bind".…”
Section: Discussionmentioning
confidence: 99%
“…As Rose and Miller have argued, "It is in this discursive field that 'the state' itself emerges as a historically variable linguistic device for conceptualizing and articulating ways of ruling" (Rose and Miller 1992, p. 177). Most nation-states in Europe have reemphasized their role as a powerful force in cultural processes and a meaningful source of legitimacy in a time when this very legitimacy of nation-states as providers of political meaning is under pressure (Geschiere 2009;Verkaaik 2010). As such, nation-states are cultural projects that present themselves through particular narratives in particular sites.…”
Section: Transnationalism and Nation-buildingmentioning
confidence: 96%
“…Previous studies in the Netherlands have indeed found large differences between municipalities in the implementation of national integration policies such as civic integration classes (Kirk 2010) and naturalization ceremonies (Verkaaik 2010). Although it is often assumed that local policies will be more accommodating, this need not be the case: indeed, local policy actors can also ignore migrant issues or seek to externalize them (Mahnig 2004).…”
Section: Diversity and Citizenshipmentioning
confidence: 97%